2018
DOI: 10.22159/ajpcr.2018.v11i11.29030
|View full text |Cite
|
Sign up to set email alerts
|

ISOLATION AND CHARACTERIZATION OF Β-Sitosterol FROM ELAEAGNUS ANGUSTIFOLIA CULTIVATED IN IRAQ

Abstract: Objective: The aim of our study was to investigate chemical constituents of leaves and seeds of Elaeagnus angustifolia since no phytochemical investigation had been done previously in Iraq.Methods: Phytochemical screening of the extracts obtained from the leaves of E. angustifolia indicated the presence of flavonoids (type of flavonols), saponins, alkaloids, steroids, and terpenoids. Thin-layer chromatography fingerprinting and the spraying reagent (concentrated H2SO4 and vanillin in ethanol) were used to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…In addition to presence of benzoic compounds such as vanillic acid in EALE, 12 there is some reports which are shown that senjed leaves contain flavonoids, alkaloids, steroids, terpenoids, as well as betasitosterol. 9 Previous studies shown that vanillic acid could decrease the insulin resistance and the hyperglycemia effectively. 22,23 Also, there are some reports which are indicate that the most of flavonoids have potent alpha-glucosidase inhibitory property and anti-hyperglycemic effect, as well as improving glucose tolerance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to presence of benzoic compounds such as vanillic acid in EALE, 12 there is some reports which are shown that senjed leaves contain flavonoids, alkaloids, steroids, terpenoids, as well as betasitosterol. 9 Previous studies shown that vanillic acid could decrease the insulin resistance and the hyperglycemia effectively. 22,23 Also, there are some reports which are indicate that the most of flavonoids have potent alpha-glucosidase inhibitory property and anti-hyperglycemic effect, as well as improving glucose tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…8 Senjed leaves contains most useful constituents such as flavonoids, alkaloids, steroids, terpenoids, as well as beta-sitosterol. 9 It has been shown that flavonoids and phenolic compounds of senjed leaves are greater than its flower, especially in methanolic and ethanolic extracts. 10 Studies have been shown that senjed fruit polysaccharide could decrease the blood glucose and lipids in diabetic rats.…”
Section: Introductionmentioning
confidence: 99%
“…Phytosterols (PS) are biologically active steroidal compounds obtained from plant foods and cholesterol is found in animals [1,2]. Beta-sitosterol, campesterol, and stigmasterol are the common phytosterols in plant and animal diet such as edible oils, nuts, cereals and citrus fruits [3,4]. These steroids have a common cholesterol skeleton with different side chains.…”
Section: Introductionmentioning
confidence: 99%
“…E. Angustifolia leaves contain most useful constituents such as flavonoids, alkaloids, steroids, terpenoids, as well as beta-sitosterol (15). It has been shown that the amount of flavonoids in E. Angustifolia leaves is more than its flower (16).…”
Section: Introductionmentioning
confidence: 99%